About absoluteness of data on elastic electron scattering with ¹²C nucleus - Buki, A.Y.; Timchenko, I.S. (Вопросы атомной науки и техники, 2007)
The results obtained in Mainz in 1982 year were check up. The analysis of data from this work was made at momentum transfer range q = 0.25 - 0.75 fm⁻¹ using the model independent form factor (the expansion of form factor in a power series of q²) and the form factor corresponding to the distribution of charge density in the shell model framework. We found a 3% systematical overestimation in Mainz data Переглядаються результати вимірювань пружного розсіяння електронів на ядрі ¹²C, виконані в Майнці (1982 р). Аналіз даних цієї роботи проводиться в діапазоні переданих імпульсів q=0.25 - 0.75 фм⁻¹ з розкладанням форм-фактора по степенях q², а також з використанням оболонкової моделі розподілу щільності заряду в ядрі. Знайдено 3% систематичне завищення результатів вимірювань даної роботи Пересматриваются результаты измерений упругого рассеяния электронов на ядре ¹²C, выполненные в Майнце (1982 г). Анализ данных этой работы проводится в диапазоне переданных импульсов q = 0.25 - 0.75 фм⁻¹ с разложением форм-фактора по степеням q², а также с использованием оболочечной модели распределения плотности заряда в ядре. Найдено 3% систематическое завышение результатов измерений рассматриваемой работы.